Mengetahui Tingkat Kematangan Buah Dengan Ultrasonik Menggunakan Logika Fuzzy - Singgih Adhimantoro (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
In this research, has been done the next usage of ultrasonic and fuzzy logic to determine fruit maturity level. Reflection of ultrasonic with different frequency are used to measure water content and fruit texture in other side fuzzy logic are used to determine the fruit maturity level depend on water content and fruit texture. The research was limited to avocado, mango and papaya. Sample of data obtained by measure 30 fruit of each kind and test it with laboratories to calibrate and also test it with human perception to prove the fact of maturity. The result of this research is device that can transmit ultrasonic signal then read the reflection of it and MatLab application to fuzzy logic processing. Accuracy and precision analyzing give the result that the sistem have a good accuracy and precision with low condition of error rate. However, analyze give not good condition of precision for the percentage of maturity level. Analyze with statistic calculation give the result that there is a strong and linear correlation between water content and fruit texture with the level of fruit maturity. The research found that the fruit in mature condition is not always having sweet taste and also the opposite.